PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL DAN PROFESIONALISME KERJA TERHADAP LOYALITAS KARYAWAN DI LP3I GROUP - Farizal Marzuki (JURNAL LENTERA BISNIS, 2018)
ABSTRACTThis study was conducted to determine how much influence the Transformational Leadership Style on Employee Loyalty in LP3I Group, determine how much influence Professionalism Working on Employee Loyalty in LP3I Group, and determine how much influence Transformational Leadership Style and Professionalism Working simultaneously on Employee Loyalty in LP3I Group. This study uses the regression method to see how big the effect of independent variables and the dependent variables. The population was employees in LP3I group that has entered a period of over 5 years of work. They are President Director of LP3I, Board of Directors and the Manager/Head Office of 60 and sampled in this study as many as 40 people. Each respondent was given a total of 35 questions. Based on the results of data processing show that the influence of Transformational Leadership Style on Employee Loyalty in LP3I Group is strong, it means that the relationship between the two variables is significant at the strong degree of confidence. And the influence of Professionalism Working on Employee Loyalty in LP3I Group is strong. It means that the relationship between the two variables is significant at the strong degree of confidence. While the influence of Transformational Leadership Style and Professionalism Working Group on LP3I Employee loyalty is strong. This suggests that the Transformational Leadership Style and Professionalism Working works well, it will further increase Employee Loyalty in LP3I Group.  Keyword : Transformational Leadership Style, Employee Loyalty, Professionalism Working